2018
DOI: 10.1002/ptr.6163
|View full text |Cite
|
Sign up to set email alerts
|

Protocatechuic acid inhibits the growth of ovarian cancer cells by inducing apoptosis and autophagy

Abstract: Protocatechuic acid (PCA), present in many fruits and vegetables, exhibited various biological activities. Here, we provided evidence that it could be developed as a potential chemotherapeutic agent against human ovarian cancer. We found that PCA treatment significantly reduced the cell viability and colony formation of OVCAR-3, SKOV-3, and A2780 cells. OVCAR-3 cells were selected as a test model system for investigating molecular mechanism. PCA treatment induced cell cycle arrest in G 2 /M phase, the activati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 26 publications
2
26
0
Order By: Relevance
“…PCA administration also led to upregulation of autophagy-related protein LC3-II and induction of GFP-LC3 puncta formation. An inhibitory efficacy of PCA on OVCAR-3 cells may be associated with increased glutathione levels and decreased intracellular ROS [20]. Furthermore, PCA was effective in penetrating cancer cells inducing lactate dehydrogenase leakage and disrupting the mitochondrial membrane potential by decreasing Na+/K+-ATPase activity in various cell lines including MCF-7, A549, HepG2, HeLa, and LNCaP cells.…”
Section: Protocatechuic Acidmentioning
confidence: 99%
“…PCA administration also led to upregulation of autophagy-related protein LC3-II and induction of GFP-LC3 puncta formation. An inhibitory efficacy of PCA on OVCAR-3 cells may be associated with increased glutathione levels and decreased intracellular ROS [20]. Furthermore, PCA was effective in penetrating cancer cells inducing lactate dehydrogenase leakage and disrupting the mitochondrial membrane potential by decreasing Na+/K+-ATPase activity in various cell lines including MCF-7, A549, HepG2, HeLa, and LNCaP cells.…”
Section: Protocatechuic Acidmentioning
confidence: 99%
“…Based on our HPLC results, four phenolic compounds, 5‐hydroxymethylfurfural (5‐HMF) (0.65 µg/mg), neochlorogenic acid (3.02 µg/mg), protocatechuic acid (0.06 µg/mg), and syringic acid (0.07 µg/mg) were identified in pectinase‐treated P. mume concentrate. Many studies have proposed that treatment with 5‐HMF (Zhao et al., ), neochlorogenic acid (Fang et al., ; Lin, Hu, Zhou, & Cheung, ), protocatechuic acid (Xie, Guo, Wang, Lei, & Yu, ), and syringic acid (Gheena & Ezhilarasan, ; Hu, Lin, Huang, & Cheung, ) exerts cancer and angiogenesis suppressive activities with regard to several tumor species. Specifically, previous studies reported that 5‐HMF (Zhao et al., ), neochlorogenic acid (Fang et al., ), protocatechuic acid (Xie et al., ), and syringic acid (Gheena & Ezhilarasan, ) inhibited proliferation of various cancer cells at the concentrations of 0.77, 1.77, 25.2, and 4.95 µg/mg, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have proposed that treatment with 5‐HMF (Zhao et al., ), neochlorogenic acid (Fang et al., ; Lin, Hu, Zhou, & Cheung, ), protocatechuic acid (Xie, Guo, Wang, Lei, & Yu, ), and syringic acid (Gheena & Ezhilarasan, ; Hu, Lin, Huang, & Cheung, ) exerts cancer and angiogenesis suppressive activities with regard to several tumor species. Specifically, previous studies reported that 5‐HMF (Zhao et al., ), neochlorogenic acid (Fang et al., ), protocatechuic acid (Xie et al., ), and syringic acid (Gheena & Ezhilarasan, ) inhibited proliferation of various cancer cells at the concentrations of 0.77, 1.77, 25.2, and 4.95 µg/mg, respectively. Furthermore, chlorogenic acid (Lin et al., ), protocatechuic acid, and syringic acid (Hu et al., ) suppressed proliferation, migration, invasion, and capillary‐like tube formation of HUVECs at a concentration 8.85, 3.85, and 4.95 µg/mL, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies have also suggested that autophagy can inhibit the growth of OC, since it has been found to promote OVCAR-3 cell death (107). By contrast, findings from another previous study suggested that inhibition of autophagy promoted the proliferation and invasion of OC cells via the PI3K/AKT/mTOR pathway (108).…”
Section: Potential Relationship Between Sirt3 and Autophagy In Ocmentioning
confidence: 98%